2021
DOI: 10.3389/fphar.2021.756975
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Patent Medicine Liuweiwuling Tablet had Potent Inhibitory Effects on Both Wild-Type and Entecavir-Resistant Hepatitis B Virus (HBV) in vitro and Effectively Suppressed HBV Replication in Mouse Model

Abstract: Liuweiwuling Tablet (LWWL) is a licensed Chinese patent medicine (approval number: Z20060238) included in the national health insurance for anti-inflammation of chronic HBV infection, whereas its anti-HBV effect remains clarification. The study aimed to clarify its antiviral effect and related mechanisms. HepG2.2.15 cells (wild-type HBV-replicating cells) and HepG2. A64 cells (entecavir-resistant HBV-replicating cells) were used for in vitro test. Hydrodynamic injection-mediated HBV-replicating mouse model was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…With a long history of wide use in the treatment of viral infections, Chinese herbal formulas, single herbs, and derived natural compounds have been reported to possess antiviral activities 17,21,32 . Among these, single herbs like Phyllanthus urinaria , Salvia Miltiorrhiza , Rheum palmatum , and Sophora flavescens and their derived natural constituents including flavonoids, phenolic acids, oxymatrine, and alkaloids have been reported having anti‐HBV activities 19,33–36 . Our recent study also showed the ethanol extract of Ranunculus japonicus Thunb.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…With a long history of wide use in the treatment of viral infections, Chinese herbal formulas, single herbs, and derived natural compounds have been reported to possess antiviral activities 17,21,32 . Among these, single herbs like Phyllanthus urinaria , Salvia Miltiorrhiza , Rheum palmatum , and Sophora flavescens and their derived natural constituents including flavonoids, phenolic acids, oxymatrine, and alkaloids have been reported having anti‐HBV activities 19,33–36 . Our recent study also showed the ethanol extract of Ranunculus japonicus Thunb.…”
Section: Discussionmentioning
confidence: 68%
“…17,21,32 Among these, single herbs like Phyllanthus urinaria, Salvia Miltiorrhiza, Rheum palmatum, and Sophora flavescens and their derived natural constituents including flavonoids, phenolic acids, oxymatrine, and alkaloids have been reported having anti-HBV activities. 19,[33][34][35][36] Our recent study also showed the ethanol extract of Ranunculus japonicus Thunb. could inhibit HBV replication at multiple steps.…”
Section: Discussionmentioning
confidence: 82%
“…Liuweiwuling Tablet has displayed potent inhibitory effects against both wild-type and ETV-resistant HBV in both in vitro and in vivo settings. 35 Maoto, also recognized as Ma Huang Tang, has been reported to suppress HBV production by impeding the incorporation of HBV nucleocapsids into virions. 36 Luteolin-7-O-glucoside, a natural compound isolated from leafy vegetable lettuce, has displayed significant reductions in HBsAg production.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, due to the complexity of Chinese medicine and the inter‐relationship of signaling pathways, TCM, especially Chinese medicine preparations, may affect most of the signaling pathways. Many outstanding studies using omics technology such as transcriptomics, 52 proteomics 53 and metabolomics have revealed the mechanisms of the anti‐inflammatory effects of TCM 54 and show that it is possible that multiple pathways may be involved in these effects.…”
Section: The Classic Mechanisms Of the Anti‐inflammatory Effects Of T...mentioning
confidence: 99%